Draft Annual Plan 2006-2007 Part-I Government of Sikkim - Planning Commission (Planning Commission, 2006)
Sikkim is a small Indian State in the eastern Himalaya with area of 7096 Sq. Km. lying between 27° 04’46"" and 28° 07’48” north latitude and 88° 58"" and 88° 55’25” east longitude. Sikkim became the 22nd State of India on 16lh May, 1975. Sikkim is one of the special category States and is also the 8th Member of the North Eastern Council. It is a unique mountainous State encircled by three different international boundaries. To its west lies Nepal, Bhutan and the Chumbi valley of the Tibetan Autonomous Region of the people's Republic of China in the east, Darjeeling Gorkha Hill Council of West Bengal in the South, and the Tibetan Plateau of the Tibetan Autonomous Region of the People’s Republic of China in the north. It extends approximately 114 km from north to south and 64 km from east to west with altitude ranging from 300 to 8598 m asl, having 447 villages comprising mainly three ethnic groups namely Lepchas, Bhutias and Nepalese.
Development Planning, Economic Reforms & North - Eastern Council Affairs Department Government of Sikkim